An examination of Mortgage-Backed Securities: are they suitable for investors to invest - Li, Jinghan (2007)
The purpose of this dissertation is providing investors a good understanding for Mortgage Backed Security (MBS) that could lead them making reasonable decision for MBS buying. In order to achieve this purpose, definition, structure and benefits of securitization are examined; Risks associated with MBSs are analyzed; MBS development (including various MBS available) in the U.S., UK and continent Europe market is reviewed; different types of MBSs are carefully evaluated, their various prioritising payment structures (cash flows) are investigated; finally, the challenging valuation of MBS is well discussed including a full presentation of the U.S. MBS value derive process. At the end, the different approaches employed by U.S and European market for prepayment estimation are compared.